Oxidação parcial direta de metano a metanol com o uso de complexos piperazínicos de ferro(III) - Berezuk, Márcio Eduardo (2010)
In this work it was synthesized six mononucleous Fe(III) pyperazine-derived complexes, both in its free form and as encapsulated form in zeolite Y made by flexible ligand methodology called "ship in a bottle". Also were tested the reproducibility of the methodology synthesizing complexes in triplicate and making a mechanical mixture of the zeolite FeY with ligands. Many physical-chemistry techniques were performed to determine the chemical structure of the complexes formed and to verify the iron atom environment (IRFT, RMN 1H e 13C, DRX, FRX, TGA/DTA, CHN elementary analysis, AAS, BET textural analysis e adsorption/desorption isotherms, DRS-UV, Mössbauer spectrometry). Experimental testes of the reaction of direct partial oxidation of methane to methanol were performed under various conditions of temperature (100-450 °C) and pressure (1-40- 70 bar), by analyzing two different compositions of the reaction mixture (9% methane; 1% oxygen; 90% Helium e 2,5% methane; 7,5% oxygen; 90% Helium), obtaining methanol as primary reaction product and the final products of methane oxidation. Reactions containing a mixture rich in methane, under the conditions investigated, only the FeY zeolite presented favorable performance to product methanol, but other oxygenates were formed with great selectivity beyond the final oxidation products. However, reactions containing a reaction mixture rich in oxygen, under the conditions investigated, were favored the methanol formation as low as the high reaction pressure. The increase pressure in the system favored the conversion increase, as well as the increase selectivity in the methanol formation, and also decreases the energy barrier required for methane conversion. Methanol was obtained from 150 °C temperature at 40 bar pressure system with the use of free catalysts. Computer simulations by the method of the minimization of Gibbs free energy indicated favorable conditions for the methanol formation, taking into account the two reaction mixtures used in the tests, in addition to temperature and pressure. The simulations show that there is room for improving conversion rates and selectivity observed by experimental tests, but to reach this objective, the reactions should be conducted in reaction routes that are far from the thermodynamic equilibrium reaction and, consequently, energy displaced for the Gibbs minimum energy.